Demystifying China’s police tactical units - Liu, Lu (International journal of law, crime and justice, 2023)
Police tactical units are the elite law enforcement teams tasked with handling the most dangerous and confrontational missions within the police force. However, little is known about who these officers are, how they are recruited, and how they perceive their role as an instrument of violence. Based on ethnographic observation and 23 semi-structured field interviews, this study reveals key features of the Chinese police tactical units by conducting sociological and psychological inquiries into the identities of these officers and how they deal with moral conflicts under overlapping social identities both as ruthless enforcers of the law and as members of society.